Breach of Confidence in the Mining Industry - Sadler, Pauline (1999)
Breach of confidence is a legal action that recognises the economic value of information. It is relevant to the mining industry because it protects confidential information, including all manner of trade secrets. This article explains what is required to bring a successful breach of confidence action, by examining cases such as Saltman Engineering Co Ltd v Campbell Engineering Co Ltd (1948) 65 RPC 203 and Surveys & Mining Ltd v Morrison [1967] VR 37, and describes how it applies to the mining industry.